How Stress Treatments Influence the Performance of Biodegradable Poly(Butylene Succinate)-Based Copolymers with Thioether Linkages for Food Packaging Applications - Siracusa, Valentina (Materials (Basel), 2017)
Biodegradable poly(butylene succinate) (PBS)-based random copolymers containing thioether linkages (P(BSxTDGSy)) of various compositions have been investigated and characterized from the gas barrier, thermal, and mechanical point of view, after food contact simulants or thermal and photoaging processes. Each stress treatment was performed on thin films and the results obtained have been compared to the same untreated film, used as a standard. Barrier properties with different gases (O(2) and CO(2)) were evaluated, showing that the polymer chemical composition strongly influenced the permeability behavior. The relationships between the diffusion coefficients (D) and solubility (S) with polymer composition were also investigated. The results highlighted a correlation between polymer chemical structure and treatment. Gas transmission rate (GTR) mainly depending on the performed treatment, as GTR increased with the increase of TDGS co-unit amount. Thermal and mechanical tests allowed for the recording of variations in the degree of crystallinity and in the tensile properties. An increase in the crystallinity degree was recorded after contact with simulant liquids and aging treatments, together with a molecular weight decrease, a slight enhancement of the elastic modulus and a decrement of the elongation at break, proportional to the TDGS co-unit content.